Pengaruh Penerapan Metode Demonstrasi Terhadap Prestasi Siswa Belajar - YETMAWATI, YETMAWATI (Komunitas Manajemen Kompetitif, 2017)
Abstract: Action research conducted with the application of the demonstration method to overcome the problem of low student achievement of learning. Through the implementation of this class action methods in primary schools and the data collected through tests and observation and analyzed using descriptive analysis. The results show that the improved understanding of fractions and their use in solving problems by elementary school students through the application of methods of demonstration. It is evident that in this study proved that the application of the method of demonstration can improve the ability of the simple fraction smoothly increased. Keywords: Methods Demonstration, Achievement